Korelasi Antara Kompetensi Profesional dan Multikultural Konselor Sekolah - Rudi Haryadi; Sanjaya Sanjaya (ILIN Institute, 2019)
This study aims to confirm the relationship between professional competence and multicultural competence of school counselors. The researchers collected data from 162 school counselors in the city of Banjarmasin who worked at the junior high school level, as well as high school / vocational school using a professional competency scale (? = 0.805) and multicultural (? = 0.889) totaling 45 items. The results of the study suggest that there is a positive and significant correlation between professional competence and multicultural school counselors in Banjarmasin City (r = 0.516; p <0.01). In addition, it was found that 3 aspects in professional competence also had a significant relationship with 2 aspects which became the domain of the multicultural competency of the school counselor. This study suggests the next researcher to re-examine the relationship between professional competence and multicultural competencies with a wider range and population to obtain a more comprehensive picture of the relationship between the two variables